Modulation of protein A binding allows single-step purification of mouse bispecific antibodies that retain FcRn binding. Issue 8 (17th November 2017) - Zwolak, Adam; Armstrong, Anthony A.; Tam, Susan H.; Pardinas, Jose R.; Goulet, Dennis R.; Zheng, Songmao; Brosnan, Kerry; Emmell, Eva; Luo, Jeffrey; Gilliland, Gary L.; Chiu, Mark L.
ABSTRACT: The increased number of bispecific antibodies (BsAb) under therapeutic development has resulted in a need for mouse surrogate BsAbs. Here, we describe a one-step method for generating highly pure mouse BsAbs suitable for in vitro and in vivo studies. We identify two mutations in the mouse IgG2a and IgG2b Fc region: one that eliminates protein A binding and one that enhances protein A binding by 8-fold. We show that BsAbs harboring these mutations can be purified from the residual parental monoclonal antibodies in one step using protein A affinity chromatography. The structural basis for the effects of these mutations was analyzed by X-ray crystallography. While the mutation that disrupted protein A binding also inhibited FcRn interaction, a bispecific mutant in which one subunit retained the ability to bind protein A could still interact with FcRn. Pharmacokinetic analysis of the serum half-lives of the mutants showed that the mutant BsAb had a serum half-life comparable to a wild-type Ab. The results describe a rapid method for generating panels of mouse BsAbs that could be used in mouse studies.